Upper-Extremity Functional Performance Tests: Reference Values for Overhead Athletes - Borms, Dorien; Cools, Ann (International Journal of Sports Medicine, 2018)
This study aimed to provide an age, gender and sport-based normative database for three functional shoulder tests: Y Balance Test – Upper Quarter (YBT-UQ), Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), and Seated Medicine Ball Throw (SMBT). A second aim was to discuss gender, age and sports differences. Finally, correlation between tests was evaluated. Overhead athletes (106 male, 100 female) between 18 and 50 years old and from three different sports (volleyball, tennis, handball) performed all functional tests. A linear mixed or regression model was applied to determine significant differences in test scores between gender, age and sports. Pearson correlation coefficients were analyzed to determine the relationship between tests. Normative values were established and divided by gender, sports and age. Results showed significant gender and age differences for all tests. For YBT-UQ, also significant side and sports differences were recorded. CKCUEST is moderately correlated with SMBT and YBT-UQ. Weak correlation was found between SMBT and YBT-UQ. In conclusion, this study provides normative data for YBT-UQ, CKCUEST and SMBT, which is clinically relevant for functionally screening overhead athletes and benchmark their performance to others from the same gender, age and sports. A combination of included tests is recommended.
Keywords: normative database; physical performance test; upper-extremity functional testing